Pernyataan Pailit Pada Penyertaan Modal di Badan Usaha Milik Negara - Widyaningtyas, Kezia Regina; Ikhwansyah, Isis; Suryanti, Nyulistiowati (Widya Yuridika, 2023)
State-Owned Enterprises (SOE) as a legal entity established and administered by the state obtained its establishment fund from state assets which are separated for BUMN. In conducting the activities to gain profit, of course, loans or legal relations are needed as supports to the business continuity. However, it is not uncommon for these legal relations causing debt. Bankruptcy institutions were formed with the aim to resolve debt matters in accordance with the principles of bankruptcy. In the practice, SOE is often being filed for bankruptcy. However, there are differences in opinions regarding SOE assets that cannot be confiscated, thus the bankruptcy filing is cancelled or rejected. This study aims to analyse the position of capital equity inclusion done by the state based on the relevant law and regulations, as well as to provide answers to the considerations of the judges in deciding the decree regarding SOE bankruptcy cases from time to time. This study implemented an analytical descriptive method and a normative juridical approach by examining the primary, secondary and tertiary legal materials. Based on the research and analysis conducted, it was found that there were several SOEs that were being filed for bankruptcy. However, in legal consideration, an inconsistency was found between the decrees of SOE bankruptcy as there was an assumption that the capital provided by the state for SOE could not be confiscated. The included capital has transformed from a public sphere to a private one which is related to the characteristics of the legal entity called separate legal entity.